Influence of symmetry breaking degrees on surface plasmon polaritons propagation in branched silver nanowire waveguides - Hua, Jiaojiao (Sci Rep, 2016)
Surface plasmon polaritons (SPPs)-based nanowire (NW) waveguides demonstrate promising potentials in the integrated nanophotonic circuits and devices. The realization of controlling SPPs propagation in NWs is significant for the performance of nanophotonic devices when employed for special function. In this work, we report the effect of symmetry breaking degrees on SPPs propagation behavior in manually fabricated branched silver NW structures. The symmetry breaking degree can be tuned by the angle between main NW and branch NW, which influences the emissions at the junction and the main NW terminal in a large extent. Our results illustrate the significance of symmetry breaking degree on SPPs propagation in NW-based waveguides which is crucial for designing the future nanophotonic circuits.